JICA LOAN ASSISTANCE TOWARDS INDONESIA'S ECONOMIC EFFORTS AMID THE COVID-19 PANDEMIC - Bastian, Tiara Putih; Ibrahim, Hilmi Rachman (Journal of Social Political Sciences, 2023)
This research aims to analyze the role of the Japan International Cooperation Agency (JICA) in Indonesia's economic recovery efforts during the COVID-19 pandemic using the conceptual framework of the Interdependence theory. Qualitative research methods are employed to delve into the adaptive decision-making processes within Indonesia's economic policies. The findings highlight the interdependent steps taken in Indonesia's economic policies and assess the effectiveness of JICA's financial assistance in facilitating a gradual economic recovery. The study depicts the crucial role of JICA as a catalyst for interdependent changes, supporting Indonesia's economic recovery efforts amid the challenges posed by COVID-19. The implications of this research provide insights for decision-makers, emphasizing the effectiveness of interdependent decision-making in crisis management. Understanding the role of external assistance, such as JICA's support, becomes crucial for designing adaptive and effective economic recovery strategies. Overall, this research contributes to a nuanced understanding of Indonesia's economic response to the pandemic, offering practical insights for future crisis management and recovery efforts within the context of Interdependence theory.